When it comes to adapting: Public policy and pig breeding family-operated farms in southern Santa Fe, Argentina - Tifni, Evangelina (2020)
The south of the province of Santa Fe, Argentina, in the heart of the Pampa region, traditionally sheltered family producers who combined grain production with pig farming. This last activity was gradually modified to the rhythm of the agricultural process. Given the relevance of this actor for the agricultural area of Pampa region, this paper shows the main transformations in the primary production subsystem within the Pig Agro-Food System (SAP), based on the various public policies implemented by national governments during the last 30 years, with emphasis on the 1990s and the period 2003-2015, which include milestones in industrialization process of the agricultural sector that determine the producer who adapts. The analysis is part of systemic studies, since this allows us to tackle a complex reality in which social and economic processes are articulated with other biological and climatic ones. The information collected arises from semi-structured interviews and interviews with contributions to life stories.